Females' Attitudes Toward Mental Illness: A Sample From Rural Istanbul, Turkey - GÜR, KAMER (KOWSAR PUBL, 2016)
Background: The beliefs, attitudes and behaviors of the society toward mentally ill patients may prevent these people from seeking help and accessing a successful treatment. Objectives: The current study aimed to investigate mental illness among Turkish females residing in rural areas and their attitudes toward mental illness. Patients and Methods: The current study was inferential cross-sectional. The population of this study consisted of 1000 households registered at the primary healthcare centre in Ademyavuz area who met the study inclusion criteria. The sample size was 387 females. Using the simple random sample selection method, certain females living in these households were included in the study. The socioeconomic status of the population in this region is low and middle-class. The adult population of the region is 10,960. Females comprise 39.8% of Ademyavuz population. The prevalence of mental illness in the district is unknown. Data were collected by face-to-face interviews using a researcher made questionnaire and the opinions about mental illness scale (OMI) in autumn 2008. The interviews were conducted at the participants' houses and lasted for 20 - 30 minutes. The females gave their informed consent and were assured that their information would be treated as strictly confidential. Results: The females in the rural research area had negative attitudes and stigmas about mental illness. The subject of the current study exhibited a total mean score of 155.6 +/- 24.5 in terms of their attitudes toward mental illness. Mean scores in the unsophisticated benevolence sub-scale were 42.5 +/- 8.2, 34.2 +/- 7.9 in the authoritarianism sub-scale, 25.5 +/- 6.3 in the mental illness ideology sub-scale, 34.0 +/- 7.4 in the social restrictiveness sub-scale, and 20.0 +/- 6.0 for the interpersonal etiology sub-scale. The current study found that individuals exhibited more positive attitudes towards mental illnesses as they got older ((Kvx2) = 19.42; P < 0.0001), married people exhibited a more positive attitude towards mental illnesses than singles did (Kvx(2) = 19.42; P < 0.0001), those who considered themselves to have a good economic status exhibited a more negative attitude towards mental illnesses compared to the ones who thought their economic status as poor or average (Kvx(2) = 5.11; P = 0.024). Conclusions: Nurses have an important role in creating and maintaining a mentally healthy society. It is advisable to provide the public with training and consultancy services within the context of primary healthcare services, especially during home visits to change the negative attitudes of individuals against the mentally ill and prevent approaches that promote social isolation and denouncement.
Keywords: Mental Illness; Mental Disorders; Females; Rural; Nurse; PUBLIC-ATTITUDES; OPINIONS; STIGMA